Deflections and Geoidal Heights Across a Seamount - Fischer, Irene (The International Hydrographic Review, 2015)
Detailed deflection- and geoid charts across the Kwajalein Atoll in the Marshall Islands are presented. They were computed from a density model of the area as deduced from observed astrogeodetic deflection values, bathymetric data, and assumed density variations below the ocean floor. This finely interpolated ground truth information provides a test area for satellite altimetry. In turn, deflections derived from satellite altimetry in oceanic regions may be interpolated similarly by this bathymetric method.